Fine morphology of the cuticle surface of Chordodes anthophorus and reinterpretation of C. aquaeductus, C. ferganensis and C. oscillatus (Gordiida Nematomorpha) - de Villalobos, Cristina; Zanca, Fernanda; Spiridonov, Sergei (Zootaxa, 2007)
We reinvestigate four species of the genus Chordodes from Central Asia and one from Georgia (Transcaucasian part of former USSR) in order to certify the taxonomic descriptions and verify the species status. By scanning electron microscopy, we demonstrate characteristic cuticular patterns for Chordodes anthophorus. The other three species, C. aquaeductus, C. ferganensis and C. oscillatus are synonymized with C. anthophorus because no differences were detected.